(4) تعميق إنتاج تقاوي الخضر Deepening local production of vegetable seeds - أ.د. هدي النمر، أ.د. حنان رجائي (معهد التخطيط القومي, 2026)
تعد الخُضر من المحاصيل الزراعية ذات الأهمية الاقتصادية والغذائية المرتفعة، وبرغم تمتع مصر بالعديد من الإمكانيات الطبيعية والمادية والعلمية والخبرة الطويلة في إنتاج تقاوي المحاصيل المختلفة، إلا أن إنتاجها المحلي من تقاوي محاصيل الخُضر لا يغطي سوى 2% من الاحتياجات السنوية. ومن ثم فإن مصر تستورد 98% من احتياجاتها من تلك التقاوي من الخارج، بما قد يحمله ذلك من مخاطر اقتصادية واجتماعية وبيئية. ويواجه تعميق إنتاج تقاوي محاصيل الخُضر محليًا العديد من المعوقات التسويقية والهيكلية والتنظيمية والإجرائية، منها غياب وضعف كفاءة العديد من التشريعات، وطول الفترة الزمنية اللازمة لتسجيل الأصناف الجديدة، وصعوبة المنافسة مع الشركات العالمية العملاقة المنتجة لتقاوي الخُضر والتي تمتلك المقومات المالية والإجرائية والفنية والعلمية لهذه الصناعة، والاندثار الوراثي وقلة التنوع الوراثي لتقاوي أصناف الخُضر المحلية، والبُعد عن الشفافية والحوكمة خلال مراحل إنتاج وتسويق تقاوي الخُضر محليًا. ولدى مصر العديد من الفرص المحفزة لإنتاج تقاوي الخُضر محليًا، يأتي في مقدمتها إطلاقها في عام 2019 للبرنامج الوطني لإنتاج تقاوي الخُضر الذي يستهدف استنباط أصناف وهجن محلية لتحل محل مثيلتها المستوردة. وذلك بجانب انضمام مصر إلى عضوية التحاد الدولي لحماية الأصناف النباتية (يوبوف)، وقرب إصدار البرلمان لقانون الأمان الحيوي الذي سيسمح باستخدام التكنولوجيا الحيوية الحديثة والتي تعد إحدى آليات إنتاج هجن سلالات ذات إنتاجية عالية ومقاومة للآفات والأمراض والظروف البيئية غير المواتية. وقد اقترحت الدراسة مجموعة من الآليات والإجراءات والسياسات في سبيل تعميق إنتاج الخُضر محليًا منها: - صياغة رؤية واضحة وخطة عمل ترتكز على أُسس علمية سليمة يأتي في مقدمتها وجود دراسة جدوى مالية واقتصادية لمشروع تعميق إنتاج الخُضر محليًا. - تأمين المقومات الأساسية اللازمة لبدء واستقرار عملية التهجين محليًا، ومنها حيازة الأصول الوراثية، والحصول على التقانات الحديثة لاستنباط التقاوي، ووجود البنية التحتية المواكبة للتطورات العالمية، وتوافر التمويل الكافي والمناسب لإجراء البحث والتطوير، وتوافر الكوادر البشرية المدربة والمؤهلة وذات الخبرة في مجال التهجين وإكثار التقاوي. - وضع مجموعة من السياسات والآليات والإجراءات الملائمة التي من شأنها: تفعيل دور مجلس التقاوي في رسم سياسات الإنتاج، وتعديل قانون الزراعة الموحد الحالي، وخفض المدة الزمنية اللازمة لتسجيل أصناف هجن تقاوي الخُضر الجديدة، وتسهيل الإجراءات الخاصة بتسجيل الأراضي للشركات الأجنبية العاملة في مجال إنتاج التقاوي وحماية حقوقهم، وتقديم الدعم والتسهيلات والحوافز اللازمة لدعم القطاع الخاص الوطني، وبناء شبكة للبيانات والمعلومات الإلكترونية الخاصة بصناعة التقاوي، وتعزيز الحوكمة والشفافية في عملية إنتاج التقاوي محليًا، ووضع آلية فعالة لمتابعة وتقييم هذا النشاط. كلمات مفتاحية: انتاج تقاوي الخضر- معوقات التعميق- سياسات التعميق. Vegetables are agricultural crops of high economic and nutritional importance. Although Egypt has many natural, material, and scientific capabilities and long experience in the production of seeds for various crops, its local production of seeds for vegetable crops covers only 2% of its annual needs. Hence, Egypt imports 98% of its needs of vegetable seeds- a situation which entails serious economic, social, and environmental risks. The deepening of vegetable seed production locally faces many marketing, structural, organizational, and procedural obstacles, including the absence and/or weakness of the efficiency of many legislations, the long time required to register new varieties, and the difficulty of competing with the giant global vegetable seed corporations which possess the financial, procedural, technical, and scientific requirements for this industry; the genetic extinction and the lack of genetic diversity of seeds of local varieties of vegetables; and absence of transparency and governance during the stages of production and marketing of seeds locally. Egypt has many opportunities to produce vegetable seeds locally. In 2019 a National Vegetable Seed Production Program was launched. The program aims to develop local varieties and hybrids of vegetable seeds to replace their imported counterparts. In addition, Egypt joined the International Union for the Protection of New Varieties of Plants (UPOV), and the Parliament is expected to issue a biosafety law that will allow the use of modern biotechnology, which is one of the mechanisms for producing hybrid strains with high productivity and resistance to pests, diseases, and unfavorable environmental conditions. The paper proposed a set of mechanisms, procedures, and policies in order to deepen local vegetable production, including: - A clear vision and action plan based on sound scientific foundations, foremost of which is the existence of a financial and economic feasibility study for the project to deepen local vegetable production. - The existence of the basic elements necessary to start and stabilize the process of crossbreeding locally, including the possession of germplasm, access to modern technologies for the generation of seeds; the presence of infrastructure facilities that keep pace with global developments; the availability of adequate and appropriate funding to conduct research and development activities; and the availability of trained, qualified, and professional human resources in the field of crossbreeding and seed multiplication. - Establishing a set of appropriate policies, mechanisms, and procedures that would activate the role of the Seed Board in drawing production policies; amending the current unified law of agriculture, reducing the time required for registering new vegetable seed hybrid varieties; facilitating procedures for land registration for foreign companies working in the field of seed production and protect their rights; providing the necessary support, facilities and incentives to Egypt’s private sector; building an electronic network of data and information for the seed industry; enhancing governance and transparency in the process of local production of seeds; and establishing an effective mechanism for monitoring and evaluating this activity.